Understanding long-term continence rates after robot-assisted laparoscopic prostatectomy – one-year follow-up on “Cognitive ability as a non-modifiable risk factor for post-prostatectomy urinary incontinence” - Reichert, Mathias; Ploeger, Hannah Maria; Uhlig, Annemarie; Strauss, Arne; Henniges, Philipp; Trojan, Lutz; Mohr, Mirjam Naomi (Frontiers in Surgery, 2022)
Purpose To evaluate long-term continence rates (12 months) in patients after robot-assisted laparoscopic prostatectomy (RALP) in relation to their cognitive ability (CoAb), which proved to be a predictor for early post-prostatectomy incontinence. Material & Methods This is the 12-month follow-up evaluation of our previously published observational single-center, prospective evaluation of 84 patients who underwent RALP as treatment of their localized prostate cancer between 07/2020 and 03/2021. Post-prostatectomy incontinence (PPI) was measured by asking patients about their 24 h pad usage, whereby 0 pads were considered continent and ≥1 pad was considered incontinent. CoAb was evaluated by performing the Mini-Mental State Examination prior to surgery. Possible predictors for PPI were evaluated using univariate and multivariable logistic regression models. Results Multivariable logistic regression analyses identified early incontinence status and nerve sparing (NS) as independent predictors for PPI after 12 months, resulting in a 5.69 times higher risk for PPI when the loss of urine was between 10 and 50 ml during the early performed pad test (one day after catheter removal) compared to 0–1 ml loss of urine [95% confidence interval (CI): 1.33–28.30, p = 0.024] and a 6.77 times higher risk for PPI, respectively, when only unilateral NS was performed compared to bilateral NS (95% CI: 1.79–30.89, p = 0.007). CoAb lost its predictive value for long-term PPI (p = 0.44). Conclusion The results of this study suggest that PPI is a dynamic, rather than a static condition with a dynamically changing pathophysiology within the first 12 months after RALP. Coping methods and therapies should adapt to this circumstance.